2018
DOI: 10.3390/genes9060282
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Mitochondrial Genome of Glyptothorax macromaculatus Provides a Well-Resolved Molecular Phylogeny of the Chinese Sisorid Catfishes

Abstract: Previous phylogenetic analyses of the Chinese sisorid catfishes have either been poorly resolved or have not included all the 12 sisorid genera. Here, we successfully assembled the first complete mitochondrial genome of the sisorid fish Glyptothorax macromaculatus. Based on this novel mitochondrial genome and previously published mitochondrial genomes in the Sisoridae, we generated maximum likelihood and Bayesian phylogenies. We dated our preferred topology using fossil calibration points. We also tested the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
4
10
0
Order By: Relevance
“…The atp8 gene with the highest averages of both Ka and Ka/Ks suggests more changes in amino acids. This is also consistent with the previously identified Ka/Ks ratios in other spiders [37], insects [36] and fishes [38]. The higher Ka/Ks values indicate that the atp8 gene might have experienced more relaxed selective constraints and accumulated more mutations, thus it would be more likely to lose its function [36].…”
Section: Discussionsupporting
confidence: 91%
“…The atp8 gene with the highest averages of both Ka and Ka/Ks suggests more changes in amino acids. This is also consistent with the previously identified Ka/Ks ratios in other spiders [37], insects [36] and fishes [38]. The higher Ka/Ks values indicate that the atp8 gene might have experienced more relaxed selective constraints and accumulated more mutations, thus it would be more likely to lose its function [36].…”
Section: Discussionsupporting
confidence: 91%
“…Evidence of positive selection, though not very common, has been observed in some fishes [ 55 , 56 ], in horses [ 57 , 58 ] and in insects [ 59 ]. Other studies have shown the important role the mitogenome plays in adapting to new environments as reviewed in Castellana et al 2011 [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ATP synthase F o subunit 6 or complex V drives the last step of oxidative phosphorylation for electron transport chain. Evidence supporting the adaptive evolution of the atp6 gene has been reported in the mitogenome of Glyptothorax macromaculatus [ 47 ], deep-sea fish [ 19 ], and deep-sea polynoids [ 20 ]. Although cob is a conserved gene, it is crucial to the ability of the mitochondria to generate energy through reversible electron transfer from ubiquinol to cytochrome c along with proton translocation.…”
Section: Discussionmentioning
confidence: 97%